Pengaruh Model Kooperatif Tipe Round Table Terhadap Keterampilan Menulis Ringkasan Siswa Sekolah Dasar Kelas V - Viesta Virgina; Dadan Djuanda; Enjang Yusup Ali (Jurnal Pena Ilmiah, 2022)
Fifth grades elementary students have not been able to create summary simply and sequentially based on writing aspects. Therefore, a learning model that could be an alternative is needed. Thisi research aimsito know the effect of cooperative model round table type in summary writing skill on fifth grade elementary students and to know the differences of students’ summary writing skill between students with the cooperative model round table type and with the conventional model. The used method was quasi-experimental nonequivalent control group design. The population were fifth grades elementary students in Situraja sub-district, Sumedang district. The samples were SDN Situraja and SDN Sukasari. The results show that: 1) the cooperative model round table type positively effects students’ skill in summary writing, 2) the enhancement of students’ skill in summary writing is better with cooperative learning round table type.